Investigation of the ageing conditions of PEEK powder for the selective laser sintering process - Yuqing Guo; Hu Chen; Sukun Tian; Yongxiang Xu; Kenan Ma; Shuai Ma; Xiang Wang; Yicha Zhang; Yuchun Sun (Virtual and Physical Prototyping, 2023)
ABSTRACTAgeing mechanism of PEEK powders at optimal powder bed temperature (Tb) and factors affecting their reusability remain unclear. This study investigated effects of gas type (air, nitrogen, and argon) and holding time (0–8 h) on physico-chemical properties of PEEK powders at optimal Tb. The hardness of sintered single-layers was measured to evaluate the quality of the parts. Results revealed that the flowability, morphology, and crystallinity of PEEK powders changed with holding time in different gases. Further, the ageing mechanism involved chain crosslinking within molecular chains in all gases but chain breakage in air. Further, laser power required for SLS decreased with the increase in holding time. However, the hardness of single-layers was stable for powders aged in argon for up to 8 h, but decreased by 7% for powders aged in nitrogen for 4 h. Severe degradation and blackening were observed for single-layers sintered in air using both virgin and aged powders.